2012
DOI: 10.1242/jcs.091157
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, capture and recycling of SCAR/WAVE and Arp2/3 complexes observed in cells by single-molecule imaging

Abstract: SummaryThe SCAR/WAVE complex drives lamellipodium formation by enhancing actin nucleation by the Arp2/3 complex. Phosphoinositides and Rac activate the SCAR/WAVE complex, but how SCAR/WAVE and Arp2/3 complexes converge at sites of nucleation is unknown. We analyzed the single-molecule dynamics of WAVE2 and p40 (subunits of the SCAR/WAVE and Arp2/3 complexes, respectively) in XTC cells. We observed lateral diffusion of both proteins and captured the transition of p40 from diffusion to network incorporation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 59 publications
8
60
1
Order By: Relevance
“…This behavior is also observed for other actin nucleation-promoting factors: N-WASP recycles faster in the presence of Arp2/3 complex binding and actin polymerization [48]. While the specific mechanisms mediating negative feedback have yet to be identified, recent evidence using XTC cells suggests that actin filaments may mechanically remove WRC from the membrane while undergoing retrograde flow [23] (Figure 1B). Actin may also potentially play an indirect role via the recruitment of actin-binding proteins to the leading edge that promote dissociation of WRC from the plasma membrane.…”
Section: The Basic Unit Of Actin Assembly—reciprocal Interactions Betmentioning
confidence: 72%
See 2 more Smart Citations
“…This behavior is also observed for other actin nucleation-promoting factors: N-WASP recycles faster in the presence of Arp2/3 complex binding and actin polymerization [48]. While the specific mechanisms mediating negative feedback have yet to be identified, recent evidence using XTC cells suggests that actin filaments may mechanically remove WRC from the membrane while undergoing retrograde flow [23] (Figure 1B). Actin may also potentially play an indirect role via the recruitment of actin-binding proteins to the leading edge that promote dissociation of WRC from the plasma membrane.…”
Section: The Basic Unit Of Actin Assembly—reciprocal Interactions Betmentioning
confidence: 72%
“…The actin cytoskeleton in motile cells is also intrinsically excitable, but in a manner that may not be dependent on upstream signals such as Ras and PIP3 [10]. While multiple feedback loops do appear to exist both within and between the signaling network and cytoskeleton [20,2327] (Figure 1B), the specific roles of each connection in modulating cell migration are not yet clear. In its most basic form, an excitable system comprises two components, one which produces fast-acting positive feedback and a second which produces slower negative feedback [28].…”
Section: The Basic Unit Of Actin Assembly—reciprocal Interactions Betmentioning
confidence: 99%
See 1 more Smart Citation
“…As originally reported using a single-molecule imaging approach (Millius et al, 2012), we also observed rare events of WRC retrograde motion, which we manually tracked to find a median speed of 0.161 µm/s (s.d.=0.036, n=13 dots from five cells); this is consistent with the notion that a portion of the WRC population is recycled through incorporation into the actin network, undergoing retrograde flow (Millius et al, 2012). However, most of the movements of these Abi-positive dots at protrusions were not (upper panel) and the detection of Sec6, Sec8, Sec5, Exo70 and Exo84 (middle panel).…”
Section: Identification Of a Forward Flow Of Wrcmentioning
confidence: 99%
“…Slowly-diffusing capping proteins have been observed by SiMS microscopy [15], which may reflect capping protein bound to slowly-diffusing actin oligomers or to the membrane. The Arp2/3 complex has also been observed to form a slowly-diffusing complex with its activators prior to attachment to the actin network [16]. However the implications of slowly-diffusing capping protein and Arp2/3 complex on the spatial distribution and turnover kinetics in the lamellipodium has not been modeled.…”
Section: Introductionmentioning
confidence: 99%